The Gothic Gamification of Diablo: A Framework for the English Composition/First-Year Writing Classroom - Munnelly, Patrick (Journal of Games, Game Art, and Gamification, 2025)
Gamification in the English composition classroom needs more research and varying approaches. This article presents a conceptual framework for gamifying the classroom, which is a model reimagining of a “skill tree” from the video game Diablo II. The framework is presented alongside elements and analyses from the game itself, with student feedback and student success data. While statistical analyses are not conducted, the game elements are extrapolated and the success rates and student comments are engaged with to support proof-of-concept. The game elements are also explored through the lens of the Gothic, which is used to assert and support a deep gamification framework, as opposed to the shallow BPL approaches of prior literature. The gothic gamified classroom asserts that this ground-up approach to the redesigned classroom should be a reincarnation of the game, as opposed to stapling a simply metaphor on top of the classroom. Essentially, this article shows how to gamify a classroom by explaining the rationale of the game, details elements of the game used and borrowed into the gamified classroom framework, and supports that framework with an explanation of proof-of-concept student feedback. All of this is presented as a framework to be further explored and tested for transference between other classrooms and disciplines.